Analysis of the Dynamics of Vegetation Cover and Land Use in Forest Management Unit 00-004 and its Surroundings on the Coast of Cameroon - Lacatuce, Kenne Tene; Momo Solefack, Marie Caroline; Tanougong, Delanot Armand; Dong Etchike, Alex Bruno; Monthe, Serge Rodrigue; Tchokomeni, Arnaud (Anuário do Instituto de Geociências, 2023)
In Cameroon, the government gives serious attention to protect Forest Management Units (FMU). Unfortunately, vegetation cover of FMU 00-004 decreases in the area as years ago due to anthropogenic pressures. The present study aimed to analyse the dynamics of the vegetation cover and land use of the FMU 00-004 and its surroundings in Cameroon, in the period between 1988-2020. Landsat images (1988, 2001 and 2020) and field investigations were used and processed by ENVI 5.3 software. 175 people around the forest were interviewed to obtain their perceptions on the causes of forest landscape degradation. In 1988, the FMU 00-004 and its surroundings consisted of seven types of land cover, the most important being dense forest, open forest and woody savannah. Cropland, building area, water area and eroded soil were less than 2%. In 2020, building area and croplands surface areas increased while dense and open forests cover decreased. Change in vegetation was more pronounced between 1988 and 2020 and the deforestation rate was 2.55%. The degradation main causes were settlements of the forest exploitation companies and agricultural practices. For sustainable production systems, landscape planning should be put in place by logging company to reduce Land use / Land cover challenges.